Characterization of Synthesized NiCo2O4 with Trisodium Citrate for Supercapacitor Material: A Preliminary Study - Andriono Manalu; Istas Pratomo Manalu; Muktar Bahruddin Panjaitan; Ady Frenly Simanullang; Parlindungan Sitorus (Science and Technology Indonesia, 2023)
Supercapacitors can be called electrostatic double-layer capacitors (EDLCs) or pseudo-capacitors based on their energy storage mechanism. Pseudo-capacitors with metal oxide electrodes that transmit electric charge offer great application power but low stability. This study aims to characterize trisodium citrate (TSC) modified NiCo2O4/rGO electrodes as a preliminary study for the NiCo2O4 nanoparticle pseudo-capacitor. The materials were characterized using SEM (Scanning Electron Microscopy), XRD (X-Ray Diffractometer), FT-Raman (Fourier Transform Raman Spectroscopy), and FTIR (Fourier Transform Infrared Spectroscopy). All of these analyses confirmed that NiCo2O4 was manufactured successfully using TSC. At XRD, the angles of 2????, namely 45.04 and 53.34°, matched the plane of the cubic phase nanorod crystals of NiCo2O4 with values of 400 and 511, respectively. In the Raman examination, the presence of rGO, which increased the crystallinity of NiCo2O4 nanoparticles, was confirmed. FTIR analysis indicated that the 1550-1600 cm−1 corresponds to a C=C functional group in an aromatic ring or a C=O ????-???? structure, and the wavenumber of 2300 cm−1 corresponds to the OH group in TSC, an alkanoate derivative. SEM analysis determined that NiCo2O4 nanoparticles with 1 mmol TSC are the ideal material for supercapacitor electrodes, as the structure is the most uniform, soft, and tidy. Further analysis is needed to confirm the stability of the modified material.